Marriage, gender and refugee migration : spousal relationships among Somali Muslims in the United Kingdom - Carver, Natasha (New Brunswick : Rutgers University Press, 2021)
This ethical and poetic ethnography analyses the upheavals to gender roles and marital relationships brought about by Somali refugee migration to the UK. Unmoored from the socio-cultural norms that made them men and women, being a refugee is described as making "everything" feel "different, mixed up, upside down." Marriage, Gender and Refugee Migration details how Somali gendered identities are contested, negotiated, and (re)produced within a framework of religious and politico-national discourses, finding that the most significant catalysts for challenging and changing harmful gender practices are a combination of the welfare system and Islamic praxis. Described as "an important and urgent monograph," this book will be a key text relevant to scholars of migration, transnational families, personal life, and gender. Written in a beautiful and accessible style, the book voices the participants with respect and compassion, and is also recommended for scholars of qualitative social research methods
Frontmatter -- Contents -- List of Transcription Symbols -- Series Foreword -- 1. Introduction -- 2. Context and Narrative: Speaking With and Speaking About -- 3. Atrocity Stories about Divorce -- 4. Personal Accounts of Relationship Breakdown -- 5. Being Responsible: Providing for Family -- 6. Doing Responsibility: Caring for Family -- 7. Somalinimo: An Existential Crisis -- 8. Regendering Somaliness in the British Context -- 9. Conclusion -- Acknowledgments -- Notes -- References -- Index
Print version record.
JSTOR
Keywords: Immigrant families -- Great Britain; Marriage -- Great Britain; Muslim families -- Great Britain; Muslims -- Great Britain -- Social conditions; Sex role -- Great Britain; Somalis -- Cultural assimilation -- Great Britain; Somalis -- Great Britain -- Social conditions; Electronic books; Familles immigrantes -- Grande-Bretagne.; Mariage -- Grande-Bretagne.; Familles musulmanes -- Grande-Bretagne.; Musulmans -- Grande-Bretagne -- Conditions sociales; Rôle selon le sexe -- Grande-Bretagne.; Livres numériques.; e-books.; SOCIAL SCIENCE -- General; Immigrant families; Marriage; Muslim families; Muslims -- Social conditions; Sex role; Great Britain; gender roles, marital relationships, spouse, spousal relationships, Somali, Somali Muslims, refugee, marriage, UK, United Kingdom, religious discourse, politico-national discourse, gender practices, welfare system, migration, transnational families, personal life, wedding, Islamic praxis, Islamic, divorce, Existential Crisis, family, children, british, Great Britain, Britain, politics of marriage, politics of marriage and migration, gender, families, family culture